Decisions on participation in music festivals: an exploratory research in Portugal - Portugal, João Pedro Valente (2022)
Purpose Music festivals offer new opportunities for leisure and tourist experiences in Portugal. Some tourists and residents, the so-called festival goers, participate and come back to these events, whereas others, the non-goers, never participate and are not willing to do so. The aim of this research is to understand the decision to participate or not based on facilitators and constraints to participate or not in a music festival, dismantling residents and tourists' attitudes. Design/methodology/approach Data were collected from 1,178 music festival goers and non-goers in Portugal. Content analysis was undertaken to depict the most important determinants of their decisions. Those determinants were categorized according to the three dimensions of factors of ecological systems theory, considering festival goers and non-goers as well as tourists and residents. Findings The results suggested that although constraints are not as often voiced as facilitators, both influence decisions that are expressed as delaying, postponing, avoiding or complying with others by participating in these events. Furthermore, the results suggested that the decision to participate or not depends on the social contexts of the festival goers or non-goers, and that these social contexts may invert their decision, be it by facilitating or constraining their participation. Research limitations/implications This research is limited to festivals in Portugal and used a qualitative analysis that may be confirmed in other countries with quantitative methods. Nevertheless, this research opens paths to discuss facilitators and constraints through ecological system theory and gives insights into this industry. Practical implications The results provide important insights for festival organizers to retain and build long-term relationships with festival goers. The results also provide insights into how to overcome the resistance which non-goers demonstrated. Social implications This research offers an in-depth and insightful understanding of individuals' attitudes towards music festivals, allowing festival demand to be better understood. Furthermore, this research proves that attendance of music festivals is mostly a socially driven behaviour. Originality/value By eliciting facilitators and constraints of the decision to participate in music festivals, considering residents and tourists, festival goers and non-goers, this study provides a deeper understanding of the decision to participate, through a theoretical framework which is rarely applied in this field.